Spontaneous bacterial peritonitis is a risk factor for renal failure requiring dialysis in waitlisted liver transplant candidates. Issue 5 (17th March 2016) - Karagozian, Raffi; Rutherford, Anna E.; Christopher, Kenneth B.; Brown, Robert S.
Abstract: Aims: To examine the relationship between and impact of spontaneous bacteria peritonitis (SBP) and renal failure requiring dialysis in waitlisted liver transplant (LT) candidates. Background: Renal failure is a common and severe complication in cirrhotic patients with SBP. Approximately one‐third of patients with SBP develop renal failure despite treatment of infection. However, the incidence of renal failure requiring dialysis in LT waitlisted patients who have developed SBP is unknown. The high mortality observed in this group has also raised debate about resource utilization in the care of these patients. Methods: Data from the United Network for Organ Sharing Standard Transplant and Research files were collected retrospectively between 1994 and 2012. The primary endpoint measured was first time initiation of dialysis while on the LT wait list. Secondary endpoints included waitlist time and mortality on wait list. Results: A total of 42, 085 patients were included. SBP at time of listing was diagnosed in 2, 352 patients (5.6%) and first time initiation of dialysis while on the wait list occurred in 2, 367 patients (6.2%). Unadjusted OR for requiring dialysis for patients listed with SBP was 1.66 (p < 0.001). When controlled for age, gender, BMI, diabetes mellitus, baseline creatinine, MELD score, serum albumin at listing, the adjusted OR for dialysis was 1.24 (p = 0.007) in waitlisted patients with SBP. Patients with SBP at time of listing had a mean waitlist time 142.1 d vs. 198.7 d in non‐SBP patients (p < 0.001). Conclusions: Spontaneous bacteria peritonitis patients have a significantly increased likelihood to require dialysis and mean shorter waitlist time. Furthermore, the combined occurrence of SBP and dialysis is a strong risk factor for all‐cause mortality while on the LT wait list.